The 33-kDa Platelet α-granule Membrane Protein (GMP-33) Is an N-terminal Proteolytic Fragment of Thrombospondin - Damas, Conchi; Vink, Tom; Nieuwenhuis, Karel H.; Sixma, Jan J. (Thrombosis and Haemostasis, 2001)
GMP-33 is a platelet membrane associated protein that is recognised by RUU-SP 1.77, an antibody raised against activated platelets. GMP-33 is predominantly associated with the membrane of platelet α-granules and it is translocated to the plasma membrane upon platelet activation (Metzelaar et al. Blood 1992; 79: 372-9). In this study we have isolated the protein by immunoaffinity chromatography. The N-terminus was sequenced and was identical to the N-terminal sequence of human thrombospondin. The protein was N-glycosylated and bound to heparin as would be expected of the N-terminal part of thrombospondin. RUU-SP 1.77 reacted only with reduced thrombospondin. Plasmin and trypsin digestion of thrombospondin yielded fragments of approximately the same size as GMP 33 that reacted with RUU-SP 1.77 after reduction. No evidence for alternative splicing was found. We postulate that GMP 33 is an N-terminal proteolytic fragment of thrombospondin that is membrane associated.
Keywords: Thrombospondin; platelet α-granule; platelet activation; platelet membrane